PENERAPAN MODEL PEMBELAJARAN OTAK ATIK OTAK (OAO) DALAM PEMBELAJARAN PERKALIAN BILANGAN BULAT MELALUI PENDAMPINGAN - Priyono; Rahmat Mulyono (STKIP Subang, 2022)
Improving teacher performance related to the learning process through this assistance aims to improve the ability of teachers to carry out the learning process using the Otak Atik Otak (OAO) learning model at teachers at SD Negeri Ngemplak, Kalibawang, Kulon Progo district. The steps used by researchers through this assistance use a type of school action research (PTS) which is carried out for 2 cycles. Where each cycle consists of 2 meetings. The improvement steps are based on research methods/procedures, which are carried out based on the stages of planning, implementation, observation, and reflection. The subject of the study was a teacher at SD Negeri Ngemplak, Kalibawang, Kulon Progo Regency, totaling 5 people. The object of study is the application of the Brain Atik Brain (OAO) learning model in mathematical learning of multiplication material. The results of preliminary observations of the quality of learning practices carried out by teachers still have many shortcomings seen in the table above the average score is: 2.36; the percentage reached 47.14%; category